خواتین کا علمی ارتقاء اوراسلامی فقہ و اجتہادمیں کردار: WOMEN'S INTELLECTUAL DEVELOPMENT AND ROLE IN ISLAMIC JURISPRUDENCE AND IJTIHAD (Al-Aasar, 2025)
This research explores the significance of Islamic jurisprudence (Fiqh) and the process of legal reasoning (Ijtihad), with a particular focus on the historical and contemporary contributions of female scholars in these domains. Utilizing a qualitative method and analytical approach, the concept of Ijtihad is analyzed both linguistically and terminologically, highlighting its pivotal role in deriving legal rulings in the absence of explicit textual evidence. A substantial part of this study is devoted to the active participation of women in Islamic legal scholarship from the Prophetic era to the modern age, outlining the scholarly contributions of prominent female figures such as Aisha bint Abi Bakr (RA), Umm Salama (RA), Maymunah (RA), Amrah bint Abdul Rahman, Aisha bint Talha, and others. Their expertise in Hadith, Qur’anic interpretation, and Fiqh is showcased, along with their roles in issuing legal opinions and mentoring male scholars. Furthermore, the study discusses the legacy of female Mujtahidat (female - those qualified for Ijtihad) during the Abbasid and Umayyad periods and the ongoing scholarly involvement of women in the contemporary Islamic world. By presenting historical precedents, the research emphasizes that women have always had a legitimate and impactful presence in Islamic legal discourse, challenging the misconception that Fiqh and Ijtihad are solely male-dominated disciplines. This paper concludes that the contributions of female scholars are not only significant but foundational in the development and continuity of Islamic jurisprudence. Their active role in shaping legal thought serves as a source of inspiration and a model for inclusive scholarly engagement in contemporary Islamic societies.